Роль торгово-промислових палат у формуванні конкурентоспроможності національних підприємств - Скуба, Вадим Юрійович; Skuba, Vadym (ЦНТУ, 2025)
Мета кваліфікаційної роботи полягає у теоретичному обґрунтуванні та практичному дослідженні ролі торгово-промислових палат у формуванні конкурентоспроможності національних підприємств, а також оцінка впливу Кіровоградської регіональної ТПП на розвиток конкурентних переваг підприємств області та розробка рекомендацій щодо підвищення ефективності її діяльності. The purpose of the qualification thesis is to provide a theoretical justification and a practical study of the role of chambers of commerce and industry in shaping the competitiveness of national enterprises, as well as to assess the impact of the Kirovohrad Regional Chamber of Commerce and Industry on the development of competitive advantages of enterprises in the region and to develop recommendations to enhance the effectiveness of its activities.
The role of chambers of commerce and industry in the forming of the competitiveness of national enterprises
Keywords: конкурентоспроможність підприємств; бізнес еко-системи; нетворкінг; enterprise competitiveness; business ecosystems; networking